Does MGNREGA Lead to Agrarian Crisis? Evidence from Andhra Pradesh - Turangi, Satyanarayana (Arthshastra Indian Journal of Economics & Research, 2017)
Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) is an ambitious public works programme which was introduced in 2006 to provide a basic safety net for the rural poor. It has already completed 10 years of its journey. This study attempted to draw some lessons from the past 10 years' experiences of MGNREGA implementation. During this journey, MGNREGA influenced the rural economy in different ways, especially, the agriculture sector, in addition to providing employment to the rural poor. So, this study mainly focused on agriculture to understand the effects of MGNREGA. The objective of the study was to analyze reasons for increasing wage rates in the agricultural sector which are influenced by MGNREGA. Increasing agricultural wages are caused by several factors along with MGNREGA. Although it couldn't be completed successfully, it broughtÂ some changes in the rural economy through setting up a floor wage rate which ultimately affected the cost of cultivation. In the process of undergoing structural changes in the economy, the MGNREGA was also responsible for agrarian crisis along with several other factors.